2013
DOI: 10.1111/j.1600-0587.2013.00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Where is positional uncertainty a problem for species distribution modelling?

Abstract: Species data held in museum and herbaria, survey data and opportunistically observed data are a substantial information resource. A key challenge in using these data is the uncertainty about where an observation is located. This is important when the data are used for species distribution modelling (SDM), because the coordinates are used to extract the environmental variables and thus, positional error may lead to inaccurate estimation of the species-environment relationship. The magnitude of this effect is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
739
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,211 publications
(830 citation statements)
references
References 66 publications
2
739
0
6
Order By: Relevance
“…Note that the host tree association of a species reflects the preference of that species and is not an exclusive category. We tested for collinearity of traits separately for saproxylic beetles and fungi using the ‘vif’ function in the add‐on package usdm (Naimi et al., ); the results indicated that none of the traits chosen had collinearity problems (all values of vif <1.7; for a correlation matrix plot, see Appendix S2). Trait data were gathered from primary literature and other publications and were also determined by authors with expertise and by external experts.…”
Section: Methodsmentioning
confidence: 99%
“…Note that the host tree association of a species reflects the preference of that species and is not an exclusive category. We tested for collinearity of traits separately for saproxylic beetles and fungi using the ‘vif’ function in the add‐on package usdm (Naimi et al., ); the results indicated that none of the traits chosen had collinearity problems (all values of vif <1.7; for a correlation matrix plot, see Appendix S2). Trait data were gathered from primary literature and other publications and were also determined by authors with expertise and by external experts.…”
Section: Methodsmentioning
confidence: 99%
“…Given such pervasive levels of data uncertainty, it is very likely that species identities and their environmental associations are frequently misinterpreted (Feeley & Silman 2010;Jansen & Dengler 2010;Naimi et al 2014). Furthermore, our documented patterns of uncertainty demonstrate that the likelihood of such misinterpretations is biased to particular taxonomic groups, geographical regions, and time periods.…”
Section: Combined Uncertaintymentioning
confidence: 98%
“…To reduce model overfitting, highly correlated variables were removed based upon variance inflation factor (VIF) values. The ‘vifstep’ function in the ‘usdm’ R package (Naimi, Hamm, Groen, Skidmore, & Toxopeus, ) was used to calculate VIF values for each variable. At each step, the variable with the highest VIF value was excluded.…”
Section: Methodsmentioning
confidence: 99%